Cortical stimulation depth of nTMS investigated in a cohort of convexity meningiomas above the primary motor cortex - Schwendner, Maximilian; Schroeder, Axel; Job, Kim; Meyer, Bernhard; Ille, Sebastian; Krieg, Sandro M. (Journal of neuroscience methods, 2024)
Background - In clinical routine, navigated transcranial magnetic stimulation (nTMS) is usually applied down to 25 mm. Yet, besides clinical experience and mathematical models, the penetration depth remains unclear. This study aims to investigate the maximum cortical stimulation depth of nTMS in patients with meningioma above the primary motor cortex, causing a displacement of the primary motor cortex away from the skull. - New method - nTMS stimulation data was reviewed regarding the maximum depth of stimulations eliciting motor-evoked potentials (MEPs). Additionally, electric field values and stimulation intensity were analyzed. - Results - Out of a consecutive cohort of 17 meningioma cases, 3 cases of meningioma located in motor-eloquent regions of the upper extremity and 3 cases of the lower extremity were analyzed after fulfilling all inclusion criteria. Regarding the upper extremity motor representations, the MEP could be elicited at a stimulation depth of up to 44 mm, with an electric field of 69 V/m. These results were found in 1 case with the maximum potential distance to the cortex being higher than the maximum stimulation depth eliciting MEPs. For the lower extremities, a maximum depth of 40 mm was recorded (electric field 64 V/m). - Comparison with existing methods - None available - Conclusions - The effect of nTMS is not limited to superficial cortical stimulation alone. Depending on electric-field intensity and focality, nTMS stimulation can be applied at a depth of 44 mm. In all cases, electric field strength was comparable and no superficial cortex with comparable electric field strength was observed to elicit MEPs.
Online verfügbar: 1. Februar 2024, Artikelversion: 9. Februar 2024
Gesehen am 14.08.2024